Educación financiera y finanzas personales: una competencia clave para el bienestar en estudiantes universitarios - Elgegren Apuela, Jose Antonio (2025)
This study addresses the importance of developing financial competencies among university students, emphasizing its significant impact on both their personal and professional lives. It is a theoretical-documentary analysis that examines previous records and evidence on financial education and personal finance. The adopted methodology was qualitative, basic in nature, with a systematic review design using the PRISMA method. A content analysis technique and an instrument based on an analysis matrix were employed. Ten relevant studies published between 2024 and 2021 in Spanish and with open access were selected. The results reveal that despite progress in understanding these topics, there are still deficiencies in integrating educational strategies that promote responsible management of economic resources. It is concluded that implementing financial education programs in university curricula is crucial to prepare young people for the challenges of a complex economic system, fostering habits of saving, planning, and informed decision-making that contribute to their overall well-being.